2014
DOI: 10.13080/z-a.2014.101.027
|View full text |Cite
|
Sign up to set email alerts
|

Obuolinio pjūklelio (Hoplocampa testudinea Klug) populiacijos tankis ir žalingumas soduose Lietuvoje, įvairių veislių obelis auginant pagal dvi ūkininkavimo sistemas

Abstract: An investigation of apple sawfly (Hoplocampa testudinea Klug 1816) (Hymenoptera: Symphyta: Tenthredinidae) populations was conducted in conventionally and organically managed apple orchards

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In the case of our study, a preference towards certain apple cultivars could also play a role in spatial distribution patterns. As was demonstrated in the study by Tamošiūnas et al (2014), certain cultivars suffered more severe infestation levels in comparison to others; however, no significant differences in sawfly numbers between cultivars were detected. Higher reproduction success or better survivability in certain cultivars may influence increase of population density and consequently, taking into account limited flying traits of apple sawfly species, aggregation around these spots.…”
Section: (2015) 77supporting
confidence: 56%
See 2 more Smart Citations
“…In the case of our study, a preference towards certain apple cultivars could also play a role in spatial distribution patterns. As was demonstrated in the study by Tamošiūnas et al (2014), certain cultivars suffered more severe infestation levels in comparison to others; however, no significant differences in sawfly numbers between cultivars were detected. Higher reproduction success or better survivability in certain cultivars may influence increase of population density and consequently, taking into account limited flying traits of apple sawfly species, aggregation around these spots.…”
Section: (2015) 77supporting
confidence: 56%
“…On the other hand, in conventional orchard, where sticky traps were deployed along rows of different cultivars, no clear distribution pattern, indicating a clear preference towards cultivars could be distinguished. A rootstock -cultivar combination also seemed to have no influence either on density or on infestation (Tamošiūnas et al, 2014). These results indicate more accidental nature of apple sawfly distribution in orchard territory than clearly influenced by certain apple phenotype.…”
Section: (2015) 77mentioning
confidence: 75%
See 1 more Smart Citation
“…Some studies indicated highly variable damage levels by secondary apple pests like apple sawfly (Tamosiunas et al, 2013;Tamošiūnas et al, 2014;2015) or green apple aphids (Raudonis et al, 2010) on different apple cultivars in the same orchard, pests were successfully controlled in our experiment by sustainable plant protection system. The activity of apple codling moth adults was determined during all seasons of our investigations (Table 3).…”
Section: Resultsmentioning
confidence: 64%
“…mancozeb (2.0) -pheromone traps for insects pheromone traps for insects pheromone traps for insects measure based on a mean number of insects captured per trap during a particular time interval (Tamosiunas et al, 2013;Tamošiūnas et al, 2014). Insecticides were applied when the density of pests was reaching the threshold of harmfulness.…”
Section: Methodsmentioning
confidence: 99%